Disrupting porcine glutaminase does not block preimplantation development and elongation nor decrease mTORC1 activation in conceptuses. Issue 5 (27th August 2021) - Chen, Paula R; Lucas, Caroline G; Cecil, Raissa F; Pfeiffer, Caroline A; Fudge, Melissa A; Samuel, Melissa S; Zigo, Michal; Seo, Heewon; Spate, Lee D; Whitworth, Kristin M; Sutovsky, Peter; Johnson, Gregory A; et al.
Abstract: Elongation of pig conceptuses is a dynamic process, requiring adequate nutrient provisions. Glutamine is used as an energy substrate and is involved in the activation of mechanistic target of rapamycin complex 1 (mTORC1) during porcine preimplantation development. However, the roles of glutamine have not been extensively studied past the blastocyst stage. Therefore, the objective of the current study was to determine if glutaminase (GLS), which is the rate-limiting enzyme in glutamine metabolism, was necessary for conceptus elongation to proceed and was involved in mTORC1 activation. The CRISPR/ Cas9 system was used to induce loss-of-function mutations in the GLS gene of porcine fetal fibroblasts. Wild type ( GLS +/+ ) and knockout ( GLS −/− ) fibroblasts were used as donor cells for somatic cell nuclear transfer, and GLS +/+ and GLS −/− blastocyst-stage embryos were transferred into surrogates. On day 14 of gestation, GLS +/+ conceptuses primarily demonstrated filamentous morphologies, and GLS −/− conceptuses exhibited spherical, ovoid, tubular, and filamentous morphologies. Thus, GLS −/− embryos were able to elongate despite the absence of GLS protein and minimal enzyme activity. Furthermore, spherical GLS −/− conceptuses had increased abundance of transcripts related to glutamine and glutamate metabolism and transport compared to filamentous conceptuses of either genotype. Differences in phosphorylation of mTORC1 components and targets were not detected regarding conceptus genotype or morphology, but abundance of two transcriptional targets of mTORC1, cyclin D1, and peroxisome proliferator-activated receptor gamma coactivator 1-alpha was increased in spherical conceptuses. Therefore, porcine GLS is not essential for conceptus elongation and is not required for mTORC1 activation at this developmental timepoint. Abstract : Knocking out glutaminase in porcine embryos does not prevent development to the blastocyst stage nor elongation of the conceptus to a filamentous morphology.